Comparison of common side effects from mood stabilizers and antipsychotics between pediatric and adult patients with bipolar disorder: a systematic review of randomized, double-blind, placebo-controlled trials. Issue 8 (3rd August 2019) - Bai, Yuanhan; Liu, Tiebang; Xu, Ahong; Yang, Haichen; Gao, Keming
ABSTRACT: Introduction : To compare common side effects of mood stabilizers (MSs) and antipsychotics in pediatric and adult bipolar disorder (BD). Area covered : MEDLINE, EMBASE, PsycINFO was searched for randomized, double-blind, placebo-controlled trials (RCTs) in the treatment of pediatric and adult BD. Twelve RCTs for pediatric patients and 30 for adult patients were included. The risk for the discontinuation due to adverse events, ≥7% weight gain, somnolence, akathisia, nausea and vomiting from a medication relative to placebo was estimated with absolute risk increase and the number needed to harm. The relative risk of these measures in pediatric and adult patients was compared. Expert opinion : Overall, the relative risk for ≥7% weight gain, somnolence, nausea, or vomiting was higher, and akathisia was lower in pediatric patients than in adults. The magnitude of difference among MSs and antipsychotics and between pediatrics and adults varied widely. The risk for pediatric patients could be underestimated because in most pediatric studies, doses of studied medications were lower and flexibly dosed, and titration speeds were slower than in adult studies. Clinicians should pay attention to differences in study designs to understand the risk for common side effects when prescribing a medication for BD.